From an increase in the number of tandem repeats through the decrease of sialylation to the downregulation of MUC1 expression level. Issue 3 (27th September 2018) - Syrkina, Marina; Viushkov, Vladimir; Potashnikova, Daria; Veiko, Vladimir; Vassetzky, Yegor; Rubtsov, Mikhail
Abstract: Enhanced glucose uptake by cancer cells was demonstrated in many studies in vitro and in vivo. Glycolysis is one of the main ways of obtaining energy in hypoxia conditions. However, in addition to energy exchange, carbohydrates are also necessary for the posttranslational modification of the protein molecules. Cancer cells are often characterized by an enhanced expression of different glycoproteides. Correct glycosylation defines the structure and activity of such molecules. We demonstrated that under the same cultivation conditions, the intensity of glycosylation does not depend on the total number of potential O ‐glycosylation sites in one molecule. As a model for the investigation, the tandem repeat region (region with variable number of tandem repeats) of the human mucin MUC1, in which each of the repeats carries four potential O ‐glycosylation sites, was used. An increase of the tandem repeat number in the recombinant protein did not lead to a proportional increase in the level of sLe a glycosides. A consequence of this was a reduction in the number of recombinant proteins associated with the cytoplasmic membrane at an overall high expression level. Prolongation of the cultivation duration led to a reduction in the expression level of the recombinant proteins by up to 30% of the initial level, and the intensity of this reduction was in a direct ratio to the number of tandem repeats in the protein molecule. Abstract : It was demonstrated that under the same cultivation conditions, an increase of the protein length leads to a decrease in the density of sLe a glycosides associated with protein core. A consequence of this was a reduction in the number of recombinant proteins associated with the cytoplasmic membrane. Prolongation of the cultivation duration led to a reduction in the expression level of the recombinant proteins.